The aporphine alkaloid boldine improves endothelial function in spontaneously hypertensive rats - Yeh-Siang, L.; Ajay, M.; Achike, F. I.; Murugan, D.; Mustafa, Mohd Rais (Frontiers Media, 2012)
Boldine, a major aporphine alkaloid found in Chilean boldo tree, is a potent antioxidant. Oxidative stress plays a detrimental role in the pathogenesis of endothelial dysfunction in hypertension. In the present study, we investigated the effects of boldine on endothelial dysfunction in hypertension using spontaneously hypertensive rats (SHR), the most studied animal model of hypertension. SHR and their age-matched normotensive Wistar-Kyoto (WKY) rats were treated with boldine (20 mg/kg per day) or its vehicle, which served as control, for seven days. Control SHR displayed higher systolic blood pressure (SBP), reduced endothelium-dependent aortic relaxation to acetylcholine (ACh), marginally attenuated endothelium-independent aortic relaxation to sodium nitroprusside (SNP), increased aortic superoxide and peroxynitrite production, and enhanced p47phox protein expression as compared with control WKY rats. Boldine treatment significantly lowered SBP in SHR but not in WKY. Boldine treatment enhanced the maximal relaxation to ACh in SHR, but had no effect in WKY, whereas the sensitivity to ACh was increased in both SHR and WKY aortas. Boldine treatment enhanced sensitivity, but was without effect on maximal aortic relaxation responses, to SNP in both WKY and SHR aortas. In addition, boldine treatment lowered aortic superoxide and peroxynitrite production and downregulated p47phox protein expression in SHR aortas, but had no effect in the WKY control. These results show that boldine treatment exerts endothelial protective effects in hypertension, achieved, at least in part, through the inhibition of NADPH-mediated superoxide production.